Über das religiöse Verhalten der Munizipalaristokratie von Sarmizegetusa - Ardevan, Radu (Studia Europaea Gnesnensia, 2017)
One can research the religious life and choices of the local aristocrats through the analysis of their private dedications only. The results prove that these people were personally less involved in the imperial cult or in the trendy exotic religions, preferring the Roman deities, mainly Jupiter and the ones defending the home, the welfare and the health.